Clinical and theoretical issues in self-injurious behavior - Jose A. Yaryura-Tobias; Maria C. Mancebo; Fugen A. Neziroglu (Brazilian Journal of Psychiatry, 1999)
This article presents an overview of pathological self-injurious behavior (SIB). Historical and cultural aspects, epidemiology, classification and clinical aspects and pathogenesis are described. The importance of comprehensive assessment of symptomatology and functions of SIB for treatment planning are discussed.